(untitled) (Bangladesh Journal of Scientific Research, 2016)
A study was conducted to unveil the socio-economic resilience of coastal communities through questionnaire survey in 14 Unions of Sandwip island against climate related disasters. Four indicators, namely (i) demography and health, (ii) living conditions, (iii) economic status and (iv) education and awareness along with 12 variables were adopted for the resilience study. The integrated resilience scores varied from 2.17 to 4.12 where almost all of the Unions have fallen into moderate category, with two at the top (e.g., Musapur and Gachhua) and two at bottom of resilience (Azimpur and Digghapar). This pragmatic approach would be beneficial for the coastal planner and decision makers to take necessary initiatives for disaster risk reduction and adaptation in a coastal community. Bangladesh J. Sci. Res. 28(2): 161-170, Dec-2015